Assessment of State Civil Servant Recruitment for Indigenous Papuans in Sorong - Saragih, Fauziah; Suswanta, Suswanta; Amal, Ikhlasul (UUM Press, 2025)
This research explores the evaluation of the recruitment of State Civil Apparatus for Indigenous Papuans in Sorong City and the obstacles experienced by the government in recruiting State Civil Apparatus for Indigenous Papuans. The recruitment process for civil servants and state civil servants must be adjusted to three indicators: job analysis, workload analysis, and needs analysis. The novelty of this research is unique because it involves Indigenous Papuans actively in the design and implementation of the recruitment process, giving them a greater role in decisions regarding human resources in the Sorong City government. The method used in this research uses a qualitative-descriptive approach. Data sources were taken from documentary observations and interviews. The findings of this research indicate that the recruitment of State Civil Apparatus for Indigenous Papuans in developing human resources for civil servants in Sorong City is in accordance with government policy and is regulated in Law Number 21 of 2001 concerning Special Autonomy for Papua. Therefore, with the government policy in place so far, the recruitment system for State Civil Apparatus (ASN) for Indigenous Papuans (OAP) is 80 percent and for non-Indigenous Papuans, 20 percent. Then, develop a welfare and justice monitoring mechanism that focuses on Indigenous Papuans who have been recruited to ensure that they get their rights and are treated fairly in the work environment. The obstacles experienced in the recruitment system for State Civil Apparatus (ASN) are the government's budget, human resources, and inadequate infrastructure